2018
DOI: 10.1002/chem.201704284
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of 2D Inorganic Nanosheets for Emerging Energy Storage System

Abstract: Among many types of nanostructured inorganic materials, highly anisotropic 2D nanosheets provide unique advantages in designing and synthesizing efficient electrode and electrocatalyst materials for novel energy storage technologies. 2D inorganic nanosheets boast lots of unique characteristics such as high surface area, short ion diffusion path, tailorable compositions, and tunable electronic structures. These merits of 2D inorganic nanosheets render them promising candidate materials as electrodes for diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 274 publications
(301 reference statements)
0
25
0
Order By: Relevance
“…To achieve a remarkable enhancement of the photocatalytic activity upon hybridization, the monolayered nanosheets prepared from the intercalation‐based exfoliation are one of the best candidates as building blocks for hybrid‐type photocatalysts. Since most of the chemically exfoliated inorganic nanosheets have sufficient surface charge, they can be easily hybridized with other species in terms of electrostatic interactions. Depending on the hybridization method, the 2D nanosheet‐based hybrid materials can be synthesized in the form of a composite powder or as multilayered thin films .…”
Section: Synthesis and Characteristics Of Exfoliated Inorganic 2d Nanmentioning
confidence: 99%
“…To achieve a remarkable enhancement of the photocatalytic activity upon hybridization, the monolayered nanosheets prepared from the intercalation‐based exfoliation are one of the best candidates as building blocks for hybrid‐type photocatalysts. Since most of the chemically exfoliated inorganic nanosheets have sufficient surface charge, they can be easily hybridized with other species in terms of electrostatic interactions. Depending on the hybridization method, the 2D nanosheet‐based hybrid materials can be synthesized in the form of a composite powder or as multilayered thin films .…”
Section: Synthesis and Characteristics Of Exfoliated Inorganic 2d Nanmentioning
confidence: 99%
“…The detail preparation of PEDOT/CP electrode was stated in our previous work [38]. The long and smooth fibers of CP orient randomly and are densely packed, forming the porous structure ( Figure 1B,C) [3,40], which is help for the coating of PEDOT and provides the channel for the ion migration. Figure 1E,F shows that the CP coated with PEDOT films (PEDOT/CP) retained the loose, porous microstructure of electrode and that there are lots of spindle-like multi-sized PEDOT distributing uniformly over individual carbon fibers.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 95%
“…Recently, electrochemical energy storage devices have received much attention due to the increasing population and the sharp depletion of fossil fuels [1][2][3][4]. Supercapacitors (SCs) are a promising green energy storage device because of their high power density, fast charge-discharge rate, long-cycle stability, and eco-friendliness [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these successes, the study of CHMCs is still in its infancy, and more advanced conned hollow nanostructures with multifunctional compositions and controlled congurations, and related mechanisms remain to be explored. Considering that previous reviews have reported diverse 2D or simple hollow structures of metal suldes and oxides, and their energy-related applications, [25][26][27][28][29] this review focuses on CHMCs and the correlation between CHMC structural features and their electrochemical behaviours, aiming at providing some insight into the design and synthesis of advanced CHMCs. The content of this review can be divided into three parts: rstly, we summarized the very recent progress in the smart architecture of CHMCs through compositional and geometrical manipulation.…”
Section: Introductionmentioning
confidence: 99%